STUDI PERBANDINGAN PARTISIPASI POLITIK PEMILIH DI KOTA TEGAL DALAM PEMILU LEGISLATIF TAHUN 2014 DAN PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 (STUDI KASUS KECAMATAN TEGAL TIMUR DAN MARGADANA) - Achmad Syauqi; Nur Hidayat Sardini; Fitriyah Fitriyah (Journal of Politic and Government Studies, 2015)
ABSTRACTIn 2014 Indonesia once again held elections to vote Legislatives, President and Vice President. Generally, Legislative Election collects a better participation number compare to Presidential Elections. But in subdistrict level, East Tegal collected more votes on Presidential Election and the highest participations rate (2,47%) among other subdisctrict. It is really the contrary of Margadana that have the biggest slump participation rate (5,08%) In Tegal on Presidential Election. This study aim is to analyse the voters political participation difference tendencies and the determine factors that affect the voters political participation on Legislative Elections and Presidential Elections in East Tegal and Margadana based on the external factors (structural and figures candidate) and internal factors (sociological, psychological, and rational choice). This study uses survey methode by distributing questionnaires to the respondents. The targets in this study are 40 voters in East Tegal and 40 voters in Margadana that selected by using cluster random sampling.The results shows there is significant difference of psychological factor on Legislative Election. The majority respondents in East Tegal tend to choose candidates while the majority respondents in Margadana tend to choose the supporting party of candidates. Whereas there is no found any difference factors that affect voter turnout in both district over Presidential Elections. In general the technical problems causes of non-voting behaviour either on Legislatif or Presidential elections in East Tegal and Margadana. The flurry of activities, unreacheable polling station from the workplace, or temporary move in tto he other city for work / study and the difficulties of changing polling station rules are the reason voters did not vote. The advice can be given to General Elections Commission(KPU) of Tegal as election organizers are expected to increase more thorough and equitable dissemination to the public, especially regarding technical at the election so as to facilitate voters in participating, especially for voters who spend more time outside the city. In addition, the Commission can strengthen the good relations to other government agencies that assist the implementation of the election, NGOs, community leaders, or volunteer in providing political education to the community. Expected with increasing political knowledge society they will be more aware of the importance of their participation in the election.Keywords: Political participation influence factors, Legislative Elections, Presidential Elections.